Membuat Undangan Digital Dengan Canva - Ardian Dwi Praba Ardian; Doni Andriansyah; Veti Apriana; Syahriani (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Digital invitations have become a popular choice due to their efficiency in spreading event information. Canva, a web-based graphic design tool, offers a simple yet comprehensive platform for creating digital invitations quickly and professionally. This study aims to explore the use of Canva in designing digital invitations, especially for users without a design background. Through practical methods and evaluations, results show that Canva enhances creativity and simplifies the process, making the creation of personalized and efficient invitations easier..